Β-FeOOH modified polyurethane foam for efficient adsorption of arsenite and arsenate from contaminated water - Qiang Li; Yifan Yao; Yingying Tang; Jinsheng Huang; Mei He; Wei Zhang (Results in Chemistry, 2025)
The prevalent issue of arsenic (As) contamination in groundwater and drinking water has become a significant global concern. While metal oxide-modified polyurethane foam (PUF) provides a cost-effective solution for arsenite [As(III)] and arsenate [As(V)] removal, the absorption mechanism by akaganeite iron oxy hydroxide β-FeOOH-PUF and its practical applications remains understudied. This investigation concentrates on the synthesis of β-FeOOH-PUF through the co-precipitation method utilizing iron chloride (FeCl3) and polyethyleneimine (PEI) as raw materials. In the quest to purify contaminated natural water sources, β-FeOOH-PUF has been employed to adsorb As(III) and As(V). Findings demonstrate successful iron deposition on the foam's surface, generating numerous positively charged FeO groups. Furthermore, the specific surface area (SSA) of β-FeOOH-PUF exceeded that of the unmodified PUF. Adsorption kinetics and isothermal adsorption analyses revealed a chemical adsorption mechanism for both As(III) and As(V) on a monolayer, with maximum adsorption capacities of 7.37 and 7.96 mg g−1, respectively. The pH range had minimal impact on adsorption efficiency, with β-FeOOH-PUF demonstrating superior performance over unmodified PUF in removing As(III) and As(V) across various pH levels. The increase in the concentrations of Cl−, SO42−, HCO3−, NO3−, and PO43− will compete for adsorption sites, change surface charge density, and significantly hinder the adsorption of As(V) by β-FeOOH-PUF. β-FeOOH-PUF can be regenerated under H2O, acidic, and alkaline conditions, offering a novel approach to treat inorganic As-contaminated water sources. Therefore, due to its abundant FeO functional groups, substantial SSA, and recyclability, β-FeOOH-PUF emerges as a highly promising adsorbent for inorganic As(III) and As(V) removal.